Life cycle assessment instructed preparation of wood-based filtration device with efficient water purification and oil reclamation by deep eutectic solvent. Issue 5 (October 2022) - Sun, Xiaohan; Yu, Qianqian; Yang, Haiyue; Wang, Xin; Yang, Zhaolin; Li, Yudong; Wang, Chengyu
Abstract: Organic oils and dyes are universal contaminants in the water environment that is exceptionally hazardous to health. However, low flux and degradation efficiency hinder those contaminants remove. Herein, the wood-based filtration device handles oily-dyed water by deep eutectic solvent (DES) treatment, exhibiting high specificity surface area and porosity. Life cycle assessment (LCA) provides evidence that the DES one-step treatment introduces fewer environmental impacts (EI) than the traditional two-step method of wood pretreatment. Moreover, DES-treated wood substrate (DTWS) decorated with palladium nanoparticles (PdNPs) shows high oil/water separation efficiency (98.9%) and excellent catalytic activity to convert MB (99.8%). Compared with numerous existing filtration membrane materials, the enhancement factors for outstanding oil/water separation and excellent catalytic performances are related to the high porosity and PdNPs content by adjusting DES treatment time. This wood-based filtration device with environmental-friendly, high flux, and excellent degradation efficiency gains optimistic expectations for practical sewage treatment application. Graphical Abstract: ga1 Highlights: Life cycle assessment was initially evaluated DES treatment. DES method improved the porosity and Pd-loaded ability of wood. Wood could be used as Pd-supporter, protector, reductant and oil barrier. The wood-based filtration device exhibits excellent oil/water separation efficiency and catalytic activity.